Effect of oxygen functional groups of reduced graphene oxide on the mechanical and thermal properties of polypropylene nanocomposites. Issue 10 (13th July 2018) - Xue, Xiaodong; Chen, Yang; Yin, Qing; Zhang, Xumin; Zhang, Wanqi; Jia, Hongbing; Xiao, Leqin; Hong, Liu
Abstract: Reduced graphene oxide (rGO) with various surface structures was prepared by reducing graphene oxide (GO) with hydrazine hydrate (N2 H4 ), sodium borohydride (NaBH4 ) andl ‐ascorbic acid, respectively. The resulting rGO were used to fabricate rGO/polypropylene (PP) nanocomposites by a melt‐blending method. The surface structure of rGO as well as multifunctional properties of rGO/PP nanocomposites were thoroughly investigated. It was shown that rGO with highest C/O ratio could be obtained by reducing GO with N2 H4 . The crystallization behaviors, tensile strength, thermal conductivity and thermal stability of rGO/PP nanocomposites were significantly improved with the increase of C/O ratio of rGO. For example, with only 1 phr (parts per hundred PP) rGO reduced by N2 H4, the degree of crystallinity, tensile strength, maximum heat decomposition temperature and thermal conductivity of PP nanocomposite were increased by 6.2%, 20.5%, 48.0 °C and 54.5%, respectively, compared with those of pure PP. Moreover, the thermal degradation kinetics indicated that the decomposition activation energy of rGO/PP nanocomposites could be enhanced by adding rGO with higher C/O ratio. © 2018 Society of Chemical Industry Abstract : The tensile strength and thermal properties of reduced graphene oxide (rGO)/polypropylene (PP) nanocomposites are obviously improved, which is mainly due to the very good dispersion of rGO with highest C/O ratio in non‐polar PP matrix.